Shelter and dwelling: A pandemic response to houselessness and community-engaged pedagogy in theological education - Jérémie-Brink, Nathan (Teaching theology and religion, 2023)
Created during the height of the COVID-19 pandemic, the Shelter Project brought together a denominational seminary, a leading state research university, a community arts organization, and a housing non-profit serving unhoused and vulnerable neighbors. As the pandemic revealed and intensified the ongoing crisis of houselessness in central New Jersey and across the United States, this project, funded by the Henry Luce Foundation, provided direct housing services, preserved the stories of unhoused and vulnerable neighbors, and offered public arts interventions promoting engagement and advocacy. This article reflects on the Shelter Project's collaborative community engagement, demonstrates how oral histories and public arts developed a project-informed pedagogy, and argues for more projects that employ community-engaged scholarship in theological higher education.